Co-creating value in urban public policy contexts: A different approach. (December 2018) - Fotino, Federica; Calabrese, Mario; Lettieri, Mattia
Abstract: Urban areas face daunting economic challenges that have increased in scope in recent years. At the same time, cities provide for opportunities for growth and value creation. The interplay of these challenges and opportunities represents an area of intervention for policymakers and researchers. However, traditional approaches to urban policy deriving from managerial and economic policy theories present difficulties mainly related to capacities to counterbalance the interests and expectations of a multitude of stakeholders participating in the value co-creation process and to allow different components to synergically contribute to the sustainability of a system. The author proposes an innovative approach to urban public policy that involves adopting the theoretical corpus of the viable systems approach ("VSA"). Urban planning is particularly analyzed as systemic components of urban areas with the aim of investigating decision-making processes that support an integrated, efficient, effective and sustainable management of territories as multidimensional, multisectoral and multi-stakeholder entities. By recovering different settings, the VSA is designed for the co-creation of value as the capacity for viable systems to increase their chances of survival in their own contexts. Value derives first from strategic decisions made to find both dyadic and context consonance. Through its strategic decisions, the governing body of the territory develops a specific system as an overall synthesis of all possible systems organized within a specific area, identifying patterns of development agreed upon by the several stakeholders of the given territory. In the dynamics of value co-creation in systemic multi-subjective organizations where levels of complexity are particularly high, research on consonance among different stakeholders is particularly important to achieve the most value for a territory. In this respect, the VSA may constitute a valid tool for finding necessary capacities to imagine evolutionary paths toward new competencies.